2012
DOI: 10.1002/humu.22094
|View full text |Cite
|
Sign up to set email alerts
|

Splice site, frameshift, and chimericGFAPmutations in Alexander disease

Abstract: Alexander disease (AxD) is a usually fatal astrogliopathy primarily caused by mutations in the gene encoding GFAP, an intermediate filament protein expressed in astrocytes. We describe three patients with unique characteristics, and whose mutations have implications for AxD diagnosis and studies of intermediate filaments. Patient 1 is the first reported case with a non-coding mutation. The patient has a splice site change producing an in-frame deletion of exon 4 in about 10% of the transcripts. Patient 2 has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Immunofluorescence revealed that, like wild-type GFAP, R416W GFAP formed a well-dispersed IF network that distributed throughout the cytoplasm (Figure 7A). The IDF GFAP, resulting from deletion and insertion mutations that cause a frameshift (Flint et al ., 2012), formed filamentous networks that tended to form bundles particularly at the cell periphery (Figure 7D, arrow). In contrast, the R88C GFAP produced a completely different staining pattern, characterized by diffuse background staining (Figure 7G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence revealed that, like wild-type GFAP, R416W GFAP formed a well-dispersed IF network that distributed throughout the cytoplasm (Figure 7A). The IDF GFAP, resulting from deletion and insertion mutations that cause a frameshift (Flint et al ., 2012), formed filamentous networks that tended to form bundles particularly at the cell periphery (Figure 7D, arrow). In contrast, the R88C GFAP produced a completely different staining pattern, characterized by diffuse background staining (Figure 7G).…”
Section: Resultsmentioning
confidence: 99%
“…The observation that R88C GFAP was cleared by gigaxonin indicates that being incorporated into a filament is not essential for gigaxonin-mediated degradation, since the nonfilamentous forms of GFAP that contained the R88C mutation were efficiently degraded. Like R88C GFAP, both R239H and ∆4 GFAP (Flint et al ., 2012) failed to self-assemble into extended IF networks, yet they were resistant to gigaxonin clearance. Given that both mutations lie within the 2A subdomain of GFAP, these results suggest that changing the precise sequence of this domain can have a dramatic effect on GFAP assembly, which is consistent with the results of previous studies (Hsiao et al ., 2005; Flint et al ., 2012; Messing et al ., 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest alteration of the GFAP gene observed in Alexander disease, the previous being a splice site mutation that caused skipping of exon 4, resulting in an internal deletion of 54 amino acids. 8 However, despite the major truncation caused by the E312ter mutation, the in vitro assays show that it still seems to act via a toxic gain rather than loss of function or haploinsufficiency.…”
mentioning
confidence: 99%
“…3,13,28 Before the present study, a nonsense mutation in GFAP has not been reported for AxD, to the best of our knowledge. The p.(E312*) mutation we reported here removes part of the 2B rod domain and the whole tail domain from the GFAP.…”
Section: Discussionmentioning
confidence: 68%